Mixed Temporal Measurement of Land Use Based on AOI Data and Thermal Data - Yiyang Hu; Hongfei Chen; Xiping Yang; Yuzheng Cui; Tianxiao Cui; Wenqing Fang (Land, 2025)
Land use mix is important for urban planning, and existing land use mix metrics frameworks have been developed comprehensively in terms of categories, distances, and attributes. However, most existing indices focus solely on the spatial dimension of land use mixing, neglecting the inherent temporal variation of land use within short time scales, which results in difficulties in comprehensively and accurately capturing the cyclical dynamic characteristics of land use. In response to this problem, this study introduces innovative modifications to the diversity indicator from the perspective of the temporal availability of land use, based on the business time characteristics of land use. Specifically, three time-sensitive indexes were proposed, including the temporal diversity index (TDI), the daily temporal diversity index (DTDI), and the temporal entropy index (TEI). With these indexes, this paper measures and analyzes the functional mix of street blocks in Xi’an City. The results of the study show that the indexes are effective in reflecting changes in the temporal dimension of the land use mix. Meanwhile, Xi’an’s land use mix pattern is more reasonable in terms of setting business hours, but the type of functional mix needs to be optimized. The proposed indicator system offers a novel perspective on the spatiotemporal mixing of land use and delivers more precise decision-making support for urban planning and management.